PERANCANGAN UI/UX SISTEM ABSENSI UMKM INDOMOM FOOD BERBASIS WEB MENGGUNAKAN GIS DENGAN METODE UCD - Yasmin, Aysia Fatmi; Nugraha, Bagja; Ridwan, Taufik (Institut Teknologi dan Bisnis (ITB) Swadharma, 2025)
In the continuously evolving digital era, the application of information technology has become key to operational efficiency, including in the management of human resources in the micro, small, and medium enterprises sector (SMEs). As a rapidly growing SME, Indomom Food struggles with the manual attendance management system's inefficiency and accuracy. To address this issue, this research aims to design a UI/UX prototype of a GIS-based web attendance system using the User Centered Design (UCD) method, which includes usage context, user and organizational needs, design solutions, and design evaluation. We expect the attendance system to use GIS to verify employee attendance based on location. The research results show that the designed system successfully meets user needs, with a System Usability Scale (SUS) score of 75 in the